Genetic variants in CARD8 but not in NLRP3 are associated with ankylosing spondylitis. (November 2013) - Kastbom, A; Klingberg, E; Verma, D; Carlsten, H; Forsblad-d'Elia, H; Wesamaa, J; Cedergren, J; Eriksson, P; Söderkvist, P
<x xml:space="preserve">Abstract</x> Objectives: The NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome is important for interleukin-1beta (IL-1β) processing as part of an innate immune response. Caspase recruitment domain family, member 8 (CARD8) is an inhibitor of nuclear factor kappa B (NF-κB) and possibly also a part of the NLRP3 inflammasome. The objective of this study was to evaluate one single nucleotide polymorphism (SNP) in CARD8 and three SNPs in NLRP3 in ankylosing spondylitis (AS) susceptibility and disease phenotype. Method: We recruited 492 AS patients from Southern Sweden fulfilling the modified New York criteria for AS, and assessed phenotypic characteristics from medical records and questionnaires. Patients with psoriasis or clinically overt inflammatory bowel disease (IBD) were excluded, as were patients without human leucocyte antigen B27 (HLA-B27). Three NLRP3 SNPs (rs35829419, rs4353135, and rs10733113) and one SNP in CARD8 (rs2043211) were genotyped by commercially available TaqMan assays, and the results compared at genotype and allele levels to those of 793 population-based controls. In a subgroup of the patients (n = 169), faecal calprotectin was assessed as a marker of subclinical intestinal inflammation. Results: The minor allele (A) of CARD8-C10X (rs2043211) was associated with a decreased risk of AS in a dominant model [odds ratio (OR) 0.74, 95% confidence interval (CI) 0.54–0.94, p = 0.012] and at the allelic level (OR 0.81, 95% CI 0.68–0.97, p = 0.02), but was not associated with levels of faecal calprotectin. There was no association regarding NLRP3 SNPs and AS susceptibility, and none of the investigated SNPs were associated with iritis, anti-tumour necrosis factor (anti-TNF) therapy, or peripheral joint involvement. Conclusion: In a Swedish population, the minor allele of CARD8-C10X is associated with a decreased risk of AS, but not with levels of faecal calprotectin or disease phenotype.